Structure and Charge Regulation Strategy Enabling Superior Cyclability for Ni‐Rich Layered Cathode Materials. Issue 52 (8th October 2021) - Huang, Wei; Li, Wenjin; Wang, Lve; Zhu, He; Gao, Min; Zhao, Huan; Zhao, Jinling; Shen, Xueling; Wang, Xiaodan; Wang, Ze; Qi, Chuanlei; Xiao, Wei; et al.
Abstract: Ni‐rich layered oxides are significantly promising cathode materials for commercial high‐energy‐density lithium‐ion batteries. However, their major bottlenecks limiting their widespread applications are capacity fading and safety concerns caused by their inherently unstable crystal structure and highly reactive surface. Herein, surface structure and bulk charge regulation are concurrently achieved by introducing high‐valence Ta 5+ ions in Ni‐rich cathodes, which exhibit superior electrochemical properties and thermal stability, especially a remarkable cyclic stability with a capacity retention of 80% for up to 768 cycles at a 1C rate versus Li/Li + . Due to the partial Ta enrichment on surface, the regulated surface enables high reversibility of Li + insertion/extraction by preventing surface Ni reduction in deep charging. Moreover, bulk charge regulation that boosts charge density and its localization on oxygen remarkably suppresses microcracks and oxygen loss, which in turn prevents the fragmentation of the regulated surface and structural degradation associated with oxygen skeleton. This study highlights the significance of an integrated optimization strategy for Ni‐rich cathodes and, as a case study, provides a novel and deep insights into the underlying mechanisms of high‐valence ions substitution of Ni‐rich layered cathodes. Abstract : Surface structure and bulk charge are regulated by introducing high‐valence Ta 5+ ions for achieving stable and safe cathodes toward high‐energy Li‐ion batteries. The critical roles of the structure and charge regulation in improving structural stability are revealed, providing a novel and integrated insight into the functional mechanisms of high‐valence ions substitution in Ni‐rich cathodes.